The Role Of The Principle Of Proportionality In Protecting Civilians During Armed Conflicts: An Analytical And Applied Study - علو, نضال (Latakia University Journal - Economic and Legal Sciences Series, 2025)
The principle of proportionality is one of the fundamental pillars of international humanitarian law. It aims to minimize harm caused by military operations to civilians in proportion to the anticipated military advantage, thereby reinforcing humanitarian commitment in armed conflicts. This principle underpins numerous rules of this law. Despite its significance, the principle has not received the attention in research and study that its crucial position in this law demands. The principle of proportionality is based on the core idea of avoiding excessive use of violence and force in certain situations. It imposes limits on states to ensure their actions are acceptable and not excessive, thereby preserving numerous humanitarian considerations and providing a high degree of protection that would otherwise be unattainable without this principle. Social, moral, and religious considerations have played a major role in the emergence of this principle. Modern literature highlights the importance of re-evaluating the application of the principle of proportionality in contemporary armed conflicts. Studies indicate that the principle requires clearer standards in light of technological advancements in military operations. At its inception, this principle emerged as religious and ethical rules imposed by peoples and nations on their own fighters. Due to the value of these rules within the cultures of nations, they became part of customary international law governing armed conflicts. Subsequently, the principle was incorporated into numerous international charters and agreements as an integral part of international humanitarian law. This study addresses the principle of proportionality as a cornerstone of international humanitarian law, clarifying its role in protecting civilians during armed conflicts. The focus is on its legal foundations, applications, and practical challenges in the context of contemporary conflicts.